Adherence to multiple micronutrient powder among young children in rural Bangladesh: a cross-sectional study Global health - Raj Angdembe, Mirak; Choudhury, Nuzhat; Raisul Haque, Mohammad; Ahmed, Tahmeed (© 2015 BioMed Central Ltd., 2016)
This article was published in BMC Public Health [© 2015 BioMed Central Ltd.] and the definite version is available at: http://bmcpublichealth.biomedcentral.com/articles/10.1186/s12889-015-1752-z